A phylogeny of Carrerapyrgota Aczél (Diptera, Pyrgotidae) - Cordeiro, Maria Leidiane Alves; Mello, Ramon Luciano (Papéis Avulsos de Zoologia, 2024)
Carrerapyrgota Aczél, 1956 is a Neotropical Diptera genus within Pyrgotidae. Currently, the genus comprise four species: C. miliaria Aczél, 1956 (type species), C. personata (Lutz & Lima, 1918), C. aczeli Mello, Lamas & Rafael, 2010, and C. bernardii Mello, Lamas & Rafael, 2010. This study investigates the phylogenetic relationships among Carrerapyrgota species, aiming to establish their monophyly as a genus. To achieve this, we conducted phylogenetic analyses based on 22 external morphological characters of adults, emploing the principle of parsimony. Analyses using both equal and implied character weighting support the monophyly of the genus, based on the following apomorphies: absence of the postscutellum, R₂₊₃ with spurious apical vein, lower calypter with a longitudinal row of bristles, and the presence of a posterior longitudinal groove on the female fore femur. The species C. aczeli, C. bernardii, and C. miliaria form a monophyletic group, supported by the synapomorphic condition of a spot on the forehead. Within this group, C. bernardii and C. miliaria are sister species, sharing the synapomorphic condition of a less sclerotized M vein, after dm-cu compared to the anterior region, as well as the homoplastic condition of a spot on the median occipital sclerite. This phylogenetic analysis reaffirms the synonymy proposed by Bernardi (1990), which treats Anapyrgota Steyskal, 1967, as a junior synonym of Carrerapyrgota. The evolutionary relationship among the species of the genus is represented as (C. personata (C. aczeli (C. bernardii, C. miliaria))). Furthermore, this study includes an updated distributional map for the genus, featuring the first record of Pyrgotinae in the Andean region.